2010
DOI: 10.1007/s10648-010-9134-7
|View full text |Cite
|
Sign up to set email alerts
|

Example-Based Learning: Integrating Cognitive and Social-Cognitive Research Perspectives

Abstract: Example-based learning has been studied from different perspectives. Cognitive research has mainly focused on worked examples, which typically provide students with a written worked-out didactical solution to a problem to study. Social-cognitive research has mostly focused on modeling examples, which provide students the opportunity to observe an adult or a peer model performing the task. The model can behave didactically or naturally, and the observation can take place face to face, on video, as a screen reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
199
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(221 citation statements)
references
References 134 publications
6
199
2
4
Order By: Relevance
“…Thus far, in educational settings, examples have mostly been used for teaching cognitive skills, and this study adds further evidence that they are useful for teaching metacognitive skills as well (see also Kitsantas et al, 2000;Zimmerman & Kitsantas, 2002). A lot of research, especially on learning from worked examples, has demonstrated that for the acquisition of problem-solving skills instruction consisting of studying examples is more effective for novices than instruction consisting of practicing problem solving (see Atkinson et al, 2000;Sweller et al, 1998;Van Gog & Rummel, 2010). In this study, we did not investigate whether training self-assessment and task-selection skills via modeling examples was more effective than training those skills in some other way, for example via practice after having been explained the assessment and selection rules (i.e., how to come to a performance assessment score and how to combine performance and mental effort scores to select a new task).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus far, in educational settings, examples have mostly been used for teaching cognitive skills, and this study adds further evidence that they are useful for teaching metacognitive skills as well (see also Kitsantas et al, 2000;Zimmerman & Kitsantas, 2002). A lot of research, especially on learning from worked examples, has demonstrated that for the acquisition of problem-solving skills instruction consisting of studying examples is more effective for novices than instruction consisting of practicing problem solving (see Atkinson et al, 2000;Sweller et al, 1998;Van Gog & Rummel, 2010). In this study, we did not investigate whether training self-assessment and task-selection skills via modeling examples was more effective than training those skills in some other way, for example via practice after having been explained the assessment and selection rules (i.e., how to come to a performance assessment score and how to combine performance and mental effort scores to select a new task).…”
Section: Discussionmentioning
confidence: 60%
“…Research on worked examples inspired by cognitive theories such as ACT-R (Anderson, 1993;Van Merriënboer & Sweller, 2005) and cognitive load theory (Sweller, 1988;Sweller et al, 1998) and research on modeling examples inspired by social learning theory (Bandura, 1986) and cognitive apprenticeship (Collins, Brown, & Newman, 1989) has shown that both of these types of example-based learning are highly effective during the initial stages of problem-solving skill acquisition (for reviews, see Atkinson, Derry, Renkl, & Wortham, 2000;Van Gog & Rummel, 2010). Whereas worked examples are primarily based on a written account of a model's problem-solving procedure, modeling examples involve observing a model performing the task, which can take a variety of forms, not only live observation, but also watching a video in which the model is visible (e.g., Braaksma, Rijlaarsdam, & Van den Bergh, 2002), a video consisting of a screen capture of the model's computer screen in which the model is not visible (though s/he can be heard when a spoken explanation of what s/he is doing is provided; e.g., McLaren, Lim, & Koedinger, 2008;Van Gog, Jarodzka, Scheiter, Gerjets, & Paas, 2009), or an animation in which the model is represented by a pedagogical agent (e.g., Atkinson, 2002;Wouters, Paas, & Van Merriënboer, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…While our hypothesis was not confirmed, including replication of our own past work, we made an interesting discovery: at least sometimes, under some conditions, students can benefit the most by learning strictly with worked examples, at least with respect to conserving their time. The worked examples of our study, however, were not static, conventional examples; rather, they were "modeling" examples [15] -live, narrated videos -that were followed by prompted self-explanation questions that had to be answered correctly by the student in order to move on. At least in the context of our domain and our materials, such a type of worked example, which trades off between example study and active problem processing, led to the best results, if not with respect to learning gains than at least with respect to learning efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Fading instructional support relies on the position that, when the learner is able to carry out the required action, the support should be gradually reduced until it is no longer needed (see Van Merriënboer and Kirschner 2013). Fading is not restricted to one specific pedagogy and has been studied, for example, with regard to collaborative learning (Bouyias and Demetriadis 2012;Tsovaltzi et al 2012;Fischer 2011), inquiry learning (McNeill et al 2006), learning for conceptual change (Biemans and Simons 1996), and worked examples (Renkl and Atkinson 2003;Van Gog and Rummel 2010). Although scientific evidence demonstrates effectiveness of fading for learning in some studies (e.g., Renkl et al 2004;Tsovaltzi et al 2010), results that are mixed (e.g., Leutner 2000;McNeill et al 2006) and even disappointing (e.g., Bouyias and Demetriadis 2012;Wecker et al 2010) are reported as well.…”
Section: Adaptive Fading Of the External Supportmentioning
confidence: 99%